Tour of Asteroids for Characterization Observations (TACO): A Planetary Defense Asteroid Tour Concept - Angela M. Stickle; Andrew S. Rivkin; Justin Atchison; Jodi Berdis; Rylie Bull; Andy Cheng; R. Terik Daly; Carolyn M. Ernst; Patrick King; Meagan Leary; Emma S. G. Rainey; Ronald J. Vervack Jr.; et al. (The Planetary Science Journal)
Asteroid impacts potentially represent a substantial threat to humanity, but one that we can plan for and mitigate. To design an effective asteroid mitigation mission, however, it is important to have as detailed knowledge of the asteroid threat as possible. Our understanding of a newly discovered object will generally derive from our understanding of the near-Earth object population, and in cases where there is no time for a reconnaissance mission prior to deflection or disruption, we may need to lean heavily on any existing data of similar objects. The Tour of Asteroids for Characterization Observations (TACO) mission concept would fill key gaps in the characterization knowledge needed to plan an effective response to an asteroid threat. A tour targeting potentially hazardous asteroids and focused on reconnaissance objectives specifically relevant for planetary defense would also test instruments and technologies (e.g., autonomous navigation, high-rate gimbals) ahead of when they are actually required in response to a threat. Testing these capabilities is identified as a need in the National Near-Earth Object Preparedness Strategy and Action Plan. The TACO tour concept is specifically designed to measure the most important asteroid properties for planetary defense, including mass, size/shape, surface and near-surface structure, presence of satellites, and composition. These measurements can be obtained using a nominal payload, including a narrow-angle camera, a thermal infrared imager, and deployed test masses for gravity science.